Sustainability Report and Leverage Analysis of Financial Performance of Companies on the Sharia Securities List - Muhammad, Ali Nur; Novi Puspitasari; Susanti Prasetyaningtyas (Journal of Management Research and Studies, 2024)
Study aim For analyze influence sustainability report and leverage against performance finance company on sector energy, goods primary consumers, goods standards, and infrastructure registered in DES. Ratio sustainability report consists from aspect economic, aspect social, aspect environment, and leverage is measured with Debt to Equity Ratio, against performance measured finances​ with ROA and ROE. Population in study This is company sector energy, goods primary consumers, goods standards, and infrastructure registered on the Sharia Securities Register, reporting report finances, and reports sustainability report. Samples obtained as many as 21 companies with use technique purposive sampling. Study This using secondary data obtained​ through Sharia Securities List website and website official. Based on results data analysis and discussion at the company energy, goods primary consumers, goods standards, and infrastructure on the Sharia Securities List for 2018-2022, then obtained Conclusion, 1) Sustainability report aspect economy influential significant to performance finance; 2) Sustainability report aspect social influential significant to performance finance; 3) Sustainability report aspect environment influential significant to performance finance; 4) Leverage matters significant to performance finance.